Bibliometric Analysis of a Research Institute: S N Bose National Centre for Basic Sciences - Adhikari, Saumen (Journal of Information and Knowledge, 2018)
Bibliometric study reflects the performance of any research institute and helps identify ways to improve research work. Monthly data has been collected from citation databases, ‘web of science’ and ‘nature index’ for the last six years analyzed to understand the progress of the research institute.